In the shadow of the rain tree: Anthropological notes from Fort Kochi - Najmrocka, Katarzyna (Studia Ecologiae et Bioethicae, 2019)
The greenery heritage of Kerala’s Fort Kochi is represented by its enormous trees, which, according to legend, remember India’s colonial past. They are living monuments of the memory, with all of their cultural contexts. The locals of Fort Kochi identify with these giant trees, which are also seen as structures of long duration. Rain trees and big banyans are equated to a mother-tree which feeds the underground roots with life-giving energy. There is a cultural analogy between the old growth of trees roots and the cultural landscape of Fort Kochi, which recalls a web-like connection of historical and cultural identity with emotional biographies that endure in the shadow of the trees. Inhabitants of Fort Kochi worship and decorate the old tree giants in an annual festival. This is a symbol of symbiotic life between a multi-cultural society and nature.